Comparison Between LASER Therapy and Radial Shock Wave Therapy on Pain, Grip Strength, and Upper Limb Function in Subjects with Chronic Lateral Epicondylitis: A Randomized Clinical Trial (International Journal of Physiotherapy, 2026)
Background: Lateral epicondylitis, with a 1-3% prevalence in the general population, is caused by overuse in sports and occupations, leading to microtears in the muscle, poor healing, and decreased function. This study aimed to compare the effectiveness of Laser therapy and RSWT in treating chronic lateral epicondylitis.Methods: In this single-blinded study, 48 subjects (50 elbows) with 22 males and 26 females aged between 30 and 50 years with Chronic Lateral Epicondylitis were randomly divided into two groups. Group A (n=25,25 elbows) with a mean age of 42.96±5.4 years received Laser therapy, and Group B (n= 23, 25 elbows) with a mean age of 43.00±5.3 years received RSWT. Both groups received the Standardized Exercise Program, the Home Exercise Program, and the Ergonomic Care for 10 sessions. Subjects were assessed at Baseline and after completion of the 10th session.Results: There was no significant difference (p>0.05) between the groups at baseline. Both groups showed statistically significant improvement (p